Availability and Use of Vaccines against COVID-19 in Pregnancy - Koirala, Saugat; Pant, Smriti; Chaudhary, Binay Kumar (Nepal Mediciti Medical Journal, 2021)
Pregnant women when infected with SARS-CoV-2 infection are more at risk of having severe outcomes including ICU admission, adverse cardiac and thromboembolic events and preterm delivery. Immunization in pregnancy has certain ethical dilemmas and vaccination seems to be challenging. Preliminary data regarding the use of mRNA based vaccines against this virus in pregnant women is promising. Recently, RCOG and WHO have widened the scope of use of vaccines among pregnant women against COVID-19. Similarly, ACOG has also given the go-ahead to the use of two mRNA based and one viral vector based vaccine in pregnant women. The scope of vaccination among pregnant and lactating women being realized in developed part of world is a promising prospect in prevention of COVID-19 infections. However, developing nations require attention from private stakeholders, health and social care organizations to ensure right of health for all.